Imaging Early Stage Axolotl Salamander Embryos Inside and Out - Crawford-Young, Susan J. (CMBES Proceedings, 2017)
Preliminary imaging all sides of amphibian embryos using time-lapse microscopy during early stage development has been accomplished. Also, Optical Coherence tomography was successfully used to image the interior of a blastocoel stage embryo. Due to the yolk in amphibian eggs they cannot be seen using confocal microscopic techniques. Using The images from the exterior of the embryo and images of the interior of the eggs will be correlated to further the study of the forces that cells experience during early development including neural plate and early brain development. This will further the study of chordate and human brain development.